Comparing Students' Evaluation of Online, Hybrid, and Face-to-Face Classes - Cindy Zhiling Tu; Joni Adkins (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This study compares students' evaluation of the effectiveness of four different class settings: face-to-face, synchronous online, asynchronous online, and hybrid. The results directly show us how students compare the four types of teaching and learning formats. Overall, students like the traditional face-to-face class the most and the asynchronous online class the least. Furthermore, students feel the hybrid class is most flexible while the face-to-face class has the least flexibility.